2011
DOI: 10.4293/108680811x13071180407474
|View full text |Cite
|
Sign up to set email alerts
|

Critical View of Safety During Laparoscopic Cholecystectomy

Abstract: The authors suggest that blunt dissection of the upper portion of Calot's space has become the preferred technique for resident training during laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 20 publications
0
56
0
2
Order By: Relevance
“…Many authors found the CVS technique to be reliable, easy to perform, and applicable in the vast majority of patients [1,2,4,6]. Furthermore, it has been found to reduce the CBD injuries even when performed by the junior surgeons with varying level of surgical skills [3,6]. This reinforces an earlier on statement that the majority of the biliary tree injuries are a consequence of the misunderstanding of an anatomy within the Calot's triangle.…”
Section: The Critical View Of Safety Technique (Cvs)mentioning
confidence: 73%
See 2 more Smart Citations
“…Many authors found the CVS technique to be reliable, easy to perform, and applicable in the vast majority of patients [1,2,4,6]. Furthermore, it has been found to reduce the CBD injuries even when performed by the junior surgeons with varying level of surgical skills [3,6]. This reinforces an earlier on statement that the majority of the biliary tree injuries are a consequence of the misunderstanding of an anatomy within the Calot's triangle.…”
Section: The Critical View Of Safety Technique (Cvs)mentioning
confidence: 73%
“…The above examples make the IA an unreliable technique. On the other hand, when delivered by an experienced surgeon, it has been found to be as safe as the "critical view of safety" technique [6].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Sticking to critical view of safety approach can help in reducing misidentification of ductal and arterial anomalies in calots triangle. 7,8 Calot's triangle is bounded by common hepatic duct, cystic duct and the cystic artery and is the component of hepaticocystic triangle. 6 Accessory hepatic ducts or small bile duct may enter the gall bladder directly from its bed.…”
Section: Discussionmentioning
confidence: 99%
“…(Strasberg and Brunt ,2010). This would have prevent accidental biliary and vascular injuries due to uncommon variations, incautious bleeding control or unclear anatomy, so The patient is protected precisely because the surgeon cannot usually achieve a misleading view (Vettoretto et al, 2011). So this technique considered as the gold standard for resident teaching, because it has a lower rate of biliary and hemorrhagic complications, has a shorter operative time, builds self-confidence, and is a simple standardized method both for complicated and uncomplicated gallbladder lithiasis .…”
Section: Cholecystectomy (Nijssen Et Al 2014)mentioning
confidence: 99%